Alternativa didáctica para la caracterización físico-química de las líneas espectrales del sol - Sánchez, Malory Johana; Pedraza, Andres Fernando (Revista Científica, 2011)
This article aims to provide a tool for the teacher in class is part of the development of a spectroscope home and so students can characterize the emission lines of the electromagnetic spectrum from the sun trying to determine its chemical composition. At the same time set out how we built a spectroscopic device to observe this phenomenon and finally the measurements obtained by students in the course of astronomy at the District University Francisco José de Caldas.